The Effect of Frying Conditions on the Physical and Chemical Quality Attributes of Clearhead Icefish (Protosalanx hyalocranius) During Deep Frying and Air Frying - Ying Li; Xiufang Xia; Guoping Yu (Foods)
The effect of frying conditions on the quality attributes of clearhead icefish under deep frying and air frying was evaluated using the Soxhlet extractor method, colorimeter, and textural analyzer. With the increasing frying temperature and time, the water loss, oil uptake, volumetric shrinkage, redness, yellowness, browning index, hardness, crispiness, the dispersion of textural data, and sensory scores in deep-fried and air-fried samples increased (p < 0.05); the lightness, whiteness, and thiobarbituric acid reactive substances (TBARS) decreased (p < 0.05), while crispiness showed no significant difference (p > 0.05). Compared to deep-fried samples, air-fried samples showed a 15.6–20.8% and 63.2–64.7% decrease in the water content and oil content, respectively. Volumetric shrinkage, hardness, and crispiness of the air-fried samples increased 30.3–68.4%, 53.5–53.7%, and 53.0–59.1%, respectively, relative to deep-fried samples. Air-fried samples displayed a decreasing uniformity in color. Therefore, frying temperature and time conferred a desirable color and texture to the fried clearhead icefish by affecting mass transfer, Maillard reactions, and lipid oxidation reactions. In addition, the difference in quality attributes between deep-fried and air-fried products was attributed to the difference in heat transfer mode. The study aims to provide a theoretical basis for the application of two frying methods and the production of high-quality fried foods.